The Biodigital Paradigm in the Universe of Superheroes: Convergence of Technology and Biology in Contemporary Narrative - Fraile Narváez, Marcelo (Cuadernos de Documentación Multimedia, 2024)
At the end of the 20th century, the aesthetic transformation in superhero cinema reflects a transition from a mechanistic approach to a deep integration with the biological, influenced by technological advances and biological discoveries. This transformation redefines the genre, providing new visual and narrative dimensions. Bio-aesthetics, as proposed by Katya Mandoki, offers a theoretical framework to understand this transition, considering aesthetics as a science of sensible knowledge based on the evolution of living beings. This perspective allows us to analyze how sensory and emotional experiences are reflected in the visual narrative of contemporary cinema.The study examines this evolution through five emblematic cases: "Superman," "Aquaman," "Spider-Man," “Wonder Woman,” and "The Avengers." Each film shows how bio-aesthetics redefines the superhero genre, using biological and technological elements to resonate with our evolutionary sensibilities. Bio-aesthetics also introduces an ethical dimension, inviting us to consider the implications of our interventions in nature. By recognizing the interconnection between biology and aesthetics, superhero films not only reflect scientific and technological advances but also explore their ethical and existential implications, offering a reflection on the impact of biotechnology in our contemporary era.
Keywords: Bio-aesthetics; Superheroes; Technology; Biology; Evolution